(untitled) (American Journal of Islam and Society, 2003)
Globalization has been a burning topic of interest for social scientists and the general public for the last 2 decades. However, a Muslim discourse on globalization has not been sufficiently developed. The current book seeks not only to present a dramatic picture of the ummah within the globalized network of mainly economic relations, but also offers policy solutions to get out of this crisis and create the Islamic ummah as an active actor in global economic and political affairs. As the title suggests, in this book globalization does not have the pos itive connotations that it has in liberal western scholarship. In fact, it is seen more as a recolonization of the Third World, and, in particular, of the Islamic world. The first chapter lays the theoretical ground, the last one concludes the argument and gives a strategic plan to counter recolonization, while the other six chapters concentrate on different aspects of globaliza tion. What comes out of the comparative analyses between the developed and the developing non-Muslim and Muslim worlds is the striking fact that Muslims score the lowest in almost all areas. Besides calling the Muslims’ attention to this disconcerting plethora of problems, the authors masterfully document how the myth of interdependence fades away, notwithstanding evidence of the unequal treatment by the "global" economic and political institutions, when the Muslims’ interests are at stake. In many instances, the economic and political variables go hand-in-hand with the informative ones that perpetuate and legitimize these unfair actions through a fundamentalist image of Muslims ...